Should tumbling E go out of date in amblyopia screening? Evidence from a population-based sample normative in children aged 3–4 years. Issue 6 (7th October 2017) - Guimaraes, Sandra; Fernandes, Tiago; Costa, Patrício; Silva, Eduardo
Abstract : Aims: To determine a normative of tumbling E optotype and its feasibility for visual acuity (VA) assessment in children aged 3-4 years. Methods: A cross-sectional study of 1756 children who were invited to participate in a comprehensive non-invasive eye exam. Uncorrected monocular VA with crowded tumbling E with a comprehensive ophthalmological examination were assessed. Testability rates of the whole population and VA of the healthy children for different age subgroups, gender, school type and the order of testing in which the ophthalmological examination was performed were evaluated. Results: The overall testability rate was 95% (92% and 98% for children aged 3 and 4 years, respectively). The mean VA of the first-day assessment (first-VA) and best-VA over 2 days' assessments was 0.14 logMAR (95% CI 0.14 to 0.15) (decimal=0.72, 95% CI 0.71 to 0.73) and 0.13 logMAR (95% CI 0.13 to 0.14) (decimal=0.74, 95% CI 0.73 to 0.74). Analysis with age showed differences between groups in first-VA (F(3, 1146)=10.0; p<0.001; η2=0.026) and best-VA (F(3, 1155)=8.8; p<0.001; η2=0.022). Our normative was very highly correlated with previous reported HOTV-Amblyopia-Treatment-Study (HOTV-ATS) (first-VA, r=0.97; best-VA, r=0.99), with 0.8 to 0.7 lines consistent overestimation for HOTV-ATS as described in literature. Overall false-positive referral was 1.3%, being specially low regarding anisometropias of ≥2 logMAR lines (0.17%). Interocular difference ≥1 line VA logMAR was not associated with age (p=0.195). Conclusions: This is the first normative for European Caucasian children with single crowded tumbling E in healthy eyes and the largest study comparing 3 and 4 years old testability. Testability rates are higher than found in literature with other optotypes, especially in children aged 3 years, where we found 5%–11% better testability rates.